1997
DOI: 10.1128/jb.179.8.2740-2747.1997
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vibrio cholerae O139 genes involved in lipopolysaccharide biosynthesis

Abstract: The sequence of part of the rfb region of Vibrio cholerae serogroup O139 and the physical map of a 35-kb region of the O139 chromosome have been determined. The O139 rfb region presented contains a number of open reading frames which show similarities to other rfb and capsular biosynthesis genes found in members of the Enterobacteriaceae family and in V. cholerae O1. The cloned and sequenced region can complement the defects in O139 antigen biosynthesis in transposon insertions within the O139 rfb cluster. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 55 publications
5
48
1
Order By: Relevance
“…A deletion in O1 El Tor C31 compared to other O1 V. cholerae in a region now identified as the MGC array has been reported in earlier studies (Barker & Clark, 1994;van Dongen & DeGraaf, 1986). Earlier studies have concluded that, unlike O139 Bengal strains, Arg3 is not derived from a V. cholerae O1 parent and has evolved independently (Stroeher et al, 1995(Stroeher et al, , 1997. This is supported by the recA phylogenetic analysis (Stine et al, 2000;Fig.…”
Section: Validation Of the Gene Cassette Size Class Profiling Techniquesupporting
confidence: 54%
“…A deletion in O1 El Tor C31 compared to other O1 V. cholerae in a region now identified as the MGC array has been reported in earlier studies (Barker & Clark, 1994;van Dongen & DeGraaf, 1986). Earlier studies have concluded that, unlike O139 Bengal strains, Arg3 is not derived from a V. cholerae O1 parent and has evolved independently (Stroeher et al, 1995(Stroeher et al, , 1997. This is supported by the recA phylogenetic analysis (Stine et al, 2000;Fig.…”
Section: Validation Of the Gene Cassette Size Class Profiling Techniquesupporting
confidence: 54%
“…WbfT has been putatively assigned the UDP-galactose-4-epimerase function (Comstock et al, 1996 ;Stroeher & Manning, 1997). WbpV also has 34n4 % identity to P. aeruginosa WbpK O& , which has been proposed to be required for the biosynthesis of UDP-Fuc2NAc (Burrows et al, 1996).…”
Section: Involvement Of Wbpv and Wbpm In Udp-quinac Synthesismentioning
confidence: 99%
“…The V. cholerae O139 serogroup first emerged in 1992 as a cause of epidemic cholera (Albert et al, 1993;Cholera Working Group, 1993). It is now believed that O139 serogroup isolates arose from an O1 strain that acquired the O139 antigen (Berche et al, 1994;Bik et al, 1995;Stroeher et al, 1997;Waldor & Mekalanos, 1994). All V. cholerae O1 and O139 serogroup isolates encode two main virulence factors: toxin co-regulated pilus (TCP) and cholera toxin (CT).…”
Section: Introductionmentioning
confidence: 99%